Challenges in the journey of breast cancer patients in Brazil - Buzaid, Antônio Carlos; Achatz, Maria Isabel; Amorim, Gilberto Luiz da Silva; Barrios, Carlos H.; Carvalho, Filomena Marino; Cavalcante, Francisco Pimentel; Conceição, Karina Gondim Moutinho da; Gobbi, Helenice; Klock, Clovis; Millen, Eduardo Camargo; Oliveira, Vilmar Marques de; Rosa, Arthur Accioly; Simon, Sérgio Daniel (Brazilian Journal of Oncology, 2020)
The mortality rate of breast cancer (BC) in Brazil is increasing. Procedures that can improve the diagnosis and treatment of BC should be discussed by specialists to improve patient survival. Experts from five different specialties involved in the diagnosis and treatment of BC discussed possible problems and solutions in this context. The discussion focused on diagnosis and treatment of early and metastatic BC. The experts approached different phases of a patient's journey and defined (1) which specialty should be involved, (2) when this specialty should act, (3) what the benefits of a multidisciplinary team might be, (4) what consequences might arise when there is no multidisciplinary team available, and (5) what possible strategies should be implemented to put the recommendations into practice in a setting of scarce resources. This text brings important insights regarding solutions that a multidisciplinary team can provide in the context of BC.
Keywords: Breast Neoplasms; Diagnosis; Interdisciplinary Communication; Treatment Outcome